Dakwah bil Lisan dan Religiousitas Generasi Milenial - Ghalda Amatullah; Agus Wahyu Triatmo (Academic Journal of Da'wa and Communication, 2023)
X-School is an association for Muslim K-popers in Indonesia. They are part of the millennial generation who study Islam with da'wah bil lisan approach. This study aims to determine influence the da'wah bil lisan method has on the religiosity of the participants of the X-School Season 4. This research is a quantitative study and uses ex post facto research design. The subjects of this study were participants in the X-Season 4 program. Data collection techniques used a questionnaire. Data were analyzed using normality test, linearity test and heteroscedasticity test. The hypothesis test used is simple linear regression. The result is known that the coefficient of determination is 40.1%. So it can be concluded that the contribution or contribution or influence given by variable X (da'wah bil lisan approach) on variable Y (religiosity) is 40.1% or in other words the use of the da'wah bil lisan approach can increase the religiosity of study participants X-School Season 4 .